The Relationship Between Mutqin Memorizing The Qur’an And A Healthy Heart (Living Qur’an Study At Pondok Tahfizh Nagari Panampuang) - Humaira, Fadhila; Taufiq, Muhammad (International Journal of Research, 2024)
This research was made using qualitative methods and this research is included in field research. In this study, researchers obtained data from various instruments, namely interviews, observation and documentation. With a qualitative descriptive approach, the analysis of the data obtained (in the form of words, pictures or behavior), the data is poured by providing an explanation or description of the situation or condition under study in the form of a narrative description. In the research that has been done, shows that: (1). The concept of mutqin memorizing the Al-Qur'an according to students at Pondok Tahfizh Nagari Panampuang, (2). The relationship between mutqin memorizing the Qur'an and a healthy heart at Pondok Tahfizh Nagari Panampuang. The results of the research show that there are 3 possibilities of this mutqin relationship, namely: 1. accommodation (accepting) means that between a healthy heart and mutqin al-Qur'an are interconnected. 2. rejection (refusal) means that there is no healthy heart relationship with rote memorization. 3. depending on the condition of the relationship between the two. Conclusion of research on the concept of mutqin Al-Qur'an memorization according to students mutqin is a strong memorization, when tested can answer it. according to the students, there are 3 answers regarding the relationship between mutqin memorization and a healthy heart, namely, 1 both have a relationship, if the heart is healthy, the memory will be more mutqin , 2. there is no second relationship, if the heart is sick, the memory is still mutqin . 3 depending on the condition of memorizing the Qur'an.